The test of reincarnation of the soul by DNA and IRIS scanner (Part Three) - Antonio Alcalá Malavé; MD; PhD (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
The test of reincarnation of the soul has only been studied through the Tibetan Book of the Dead [1], written by Padmasambhava in the 8th century. He was the founder of the Nyingma school of Tibetan Buddhism and the inner tantras in the 8th century. This book is a handbook for those who have died and which, according to the Tantric Buddhism of Tibet [2], would allow achieving enlightenment during the immediate period after the death and for a few days more in order to avoid rebirthing and entering samsara again, as it is considered that the death process after dying takes 49 days and afterwards a rebirth suddenly happens in the reincarnation cycle. The content of the book gives some advice to keep in mind during this "intermediate period", known by the Tibetans as bardo [1], in order to not reincarnate in any of the called lower kingdoms according to the Buddhist tradition [2]. According to that tradition, this text is considered as one of the "earth treasures" (gter ma). Nevertheless, Padmasambhava [3] did not make it public but he concealed it, though it was discovered in a cave by Karma Lingpa 6 centuries later, in the 14th century. In the Western world it was made public for the first time trough the translation into English by Walter Evans-Wentz in 1927 [4]. These article series resolves, using the same technique, researching the process of reincarnation of the soul understanding that there are phenomena that can never be taken to the laboratory and which do not follow the entitled scientific method